Post-partum anoestrus in tropical beef cattle: A systems approach combining gene expression and genome-wide association results - Fortes, Marina R. S.; Suhaimi, Ainu H. M. S.; Porto-Neto, Laercio R.; McWilliam, Sean M.; Flatscher-Bader, Trudi; Moore, Stephen S.; D'Occhio, Michael J.; Meira, Camila Tângari [UNESP]; Thomas, Milton G.; Snelling, Warren M.; Reverter, Antonio; Lehnert, Sigrid A. (Elsevier B.V., 2014)
The length of the post-partum anoestrous interval affects reproductive efficiency in many tropical beef cattle herds. In this study, results from genome-wide association studies (Experiment 1: GWAS) and gene expression (Experiment 2: microarray) were combined in a systems approach to reveal genetic markers, genes and pathways underlying the physiology of post-partum anoestrus in tropically adapted cattle. The microarray study measured the expression of 13,964 genes in the hypothalamus of Brahman cows. A total of 366 genes were differentially expressed (DE) in the post-partum period, when acyclic cows were compared to cows that had resumed ovarian cycles. Associated markers (P < 0.05) from a high density GWAS pointed to 2829 genes that were associated with post-partum anoestrous interval (PPAI) in two populations of beef cattle: Brahman and Tropical composite. Together the experiments provided evidence for 63 genes that are likely to influence the resumption of ovulation post-partum in tropically adapted beef cattle. Functional annotation analysis revealed that some of the 63 genes have known roles in hormonal activity, energy balance and neuronal synapse plasticity. Polymorphisms within candidate genes identified by this systems approach could have biological significance in post-partum anoestrus and help select Zebu (Bos indicus) influenced cattle with genetic potential for shorter post-partum anoestrus. Crown Copyright (C) 2014 Published by Elsevier B.V. All rights reserved.
Keywords: Zebu; Hypothalamus; Genomics; Microarray; Anoestrus; Fertility